Evaluating the Role of Governance in Boosting Human Capital to Shrink Income Inequality in Developing Countries - Hossain, Tanbir (Universitas Airlangga, 2022)
Most of the developing countries in the world are facing a well-known challenging factor-like income inequality that affects the issue of balanced growth and welfare. The core goal of this paper is to investigate whether the Human Capital Index (HCI) joined with Good Governance (GG) variables have a significant impact on reducing income inequality in upper middle income (UMI) and lower middle income (LMI) countries or not. The first point is to investigate the relationship between HCI and income inequality and the second one is to find out the joint effect (HCI and GG) on income inequality (Gini Coefficient). The author divides all the countries based on income levels like UMI and LMI countries according to WB. For the UMI, HCI has no significant positive impact on reducing income inequality. However, if HCI works combined with good governance indicators like (HCI*RL), (HCI*RQ), and (HCI*GE), these interacted variables do not have significant power to reduce income inequality in UMI countries. Contrarily, for LMI countries, HCI helps to diminish income inequality significantly. When citizens achieve technical and educational qualifications, it helps them earn more money and shrinks income inequality significantly. Moreover, when HCI joints with good governing variables like PS, RQ, and RL that help to reduce income inequality significantly in LMI countries. There are some significant differences between UMI and LMI in foreign investment, job opportunities, foreign investment, and macroeconomic conditions that generate income-gap. This analysis finds that LMI countries grab influential effect in reducing income inequality in their economy compared to UMI countries.